Dismissals based on operational requirements in the workplace - Ramafalo, Mahodiela Rodney (My University, 2013)
The coming into power of the democratic government played an important role in transforming South African labour law system. After the Labour Relations Act 66 of 1995 (LRA) was implemented on 11 November 1996, the old Labour Relations Act of 1956 was repealed. The law on retrenchment forms an integral part of law of dismissals. The South African labour market has in the past years been characterized by restructuring and consequently retrenchment of employees. In most cases, employer’s decisions to retrench were challenged by the employees and unions in courts. Section 189 of the LRA stipulates procedures to be followed by an employer when contemplating dismissal of one or more employees for reasons based on operational requirements. The employer does not only have to follow the procedures set out in section 189 to render dismissals for operational reasons fair, but there must also be a valid reason to dismiss. The courts have always not been willing to second-guess the employer’s decision to retrench provided that the decision is made in good faith.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2013
Keywords: Dismissals; Retrenchments; Employees -- Dismissal of -- Law and legislation; Unfair labor practices -- South Africa